When life nearly died : the greatest mass extinction of all time - Benton M J Michael J (New York : Thames & Hudson, 2003)
Today it is common knowledge that the dinosaurs were wiped out by a meteorite impact 65 million years ago that killed half of all species then living. Far less well-known is a much greater catastrophe that took place at the end of the Permian period 251 million years ago: at least 90 percent of life was destroyed, both on land and in the sea. ... This book documents not only what happened during this gigantic mass extinction but also the recent rekindling of the idea of catastrophism.-Dust jacket.
Geological time-scale -- Antediluvian Sauria -- Murchison names the permian -- Death of catastrophism -- Concept that dared not speak its name -- Impact! -- Diversity, extinction and mass extinction -- Homing in on the event -- Life's biggest challenge -- Tale of two continents -- On the river Sakmara -- What caused the biggest catastrophe of all time? -- Sixth mass extinction? -- Glossary.
Includes bibliographical references (p. 318-328) and index.
Keywords: Extinction Biology -- History; Catastrophes Geology; Geology Stratigraphic -- Permian